Use of Foreign Methods in Preschool Educational Organizations - Jabborova Mohina Ulug'bek qizi (Genius Journals, 2023)
This paper makes analyses of the modern methods of preparing the children on Preschool educational organizations. On these cases, different research points of the innovative research were mentioned on preschool educational organizations. It concludes with the different research analyses to make better investigations in further.
Keywords: Preschool education; modern method; innovative method; effectiveness of the method